General recommendations for the management of surgical conditions during the COVID-19 pandemic (SARS-CoV-2 infection) - Ortiz, Enrique; Herrera, José R.; Algieri, Rubén D.; Tortosa, José L. (Revista Argentina de Cirugía, 2021)
These recommendations are subject to continuous review and were based on those given by the Asociación Española de Cirujanos, the American College of Surgeons, and the National Ministry of Health of Argentina.